SIFAT PAPAN WOL KAYU DARI 6 JENIS KAYU HUTAN TANAMAN INDUSTRI - I M Sulastiningsih; Rodjak Memed; Paribotro Sutigno (Jurnal Penelitian Hasil Hutan, 1990)
The results  of  laboratory test of wood wool board properties made from 6 individual  wood  species obtained from East  Kalimantan, Jambi, South Sumatera and Maluku  province   are reported  in  this paper. The properties tested were board density, moisture content,   thickness  reduction  due to compression  and bending strength.The study   reveals that  average yield  of  wood  wool  is  348  kg per  cubic  meter  of log input. The wood  wool of Acacia mangium must be soaked  in  cold  water  for  24  hours  prior to  manufacturing  of  wood  wool  board, whereas  the other species can be processed  directly.The  physical and  mechanical  properties of  wood  wool  boards  made  from  three  wood  species (Shorea platyclados, Acacia mangium and Shorea leprosulaf) catalyzed with  CaCl2 solution were in conformity with  the DIN 1101  standard Nevertheless, only two  species  (S. platyclados and A. mangium) catalyzed with Ca(OH)2 suspension met the  standard requirement.